Psychobiobehavioral Model for Preterm Birth in Pregnant Women in Low- and Middle-Income Countries. - Premji, Shahirose S.; Yim, Ilona S.; Dosani (Mawji), Aliyah; Kanji, Zeenatkhanu; Sulaiman, Salima; Musana, Joseph W.; Samia, Pauline; Shaikh, Kiran; Letourneau, Nicole; MiGHT Group (BioMed Research International, 2015)
Preterm birth (PTB) is a final common outcome resulting from many interrelated etiological pathways; of particular interest is antenatal psychosocial distress (i.e., stress, anxiety, and depression). In LMI countries, both exposure to severe life stressors and rate of PTB are on average greater when compared with high-income countries. In LMI countries women are exposed to some of the most extreme psychosocial stress worldwide (e.g., absolute poverty, limited social resources). High prevalence of antenatal stress and depression have been observed in some studies from LMI countries. We propose a psychosocial, biological, and behavioral model for investigating the complex multisystem interactions in stress responses leading to PTB and explain the basis of this approach. We discuss ethical considerations for a psychosocial, biological, and behavioral screening tool to predict PTB from a LMI country perspective.